2016
DOI: 10.1089/ast.2015.1464
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Extant Life on Mars and Its Possible Detection by the Viking Labeled Release Experiment

Abstract: The 1976 Viking Labeled Release (LR) experiment was positive for extant microbial life on the surface of Mars. Experiments on both Viking landers, 4000 miles apart, yielded similar, repeatable, positive responses. While the authors eventually concluded that the experiment detected martian life, this was and remains a highly controversial conclusion. Many believe that the martian environment is inimical to life and the LR responses were nonbiological, attributed to an as-yet-unidentified oxidant (or oxidants) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 47 publications
(65 reference statements)
0
54
0
Order By: Relevance
“…Two Viking landers carried out a series of biological experiments, including the labeled release experiment, which was designed to detect metabolic activity. In this experiment, simple 14 C‐labeled substrates, water, and Martian soil were combined and monitored for the evolution of radioactive gases (Levin and Stratt ) as evidence that microorganisms had metabolized the substrate. Viking instruments detected 14 C labeled gas; however, it is widely accepted that those data were due to oxidizing agents in the regolith rather than microbial activity (Lasne et al.…”
Section: Objective 2: Assess and Interpret The Potential Biological Hmentioning
confidence: 99%
“…Two Viking landers carried out a series of biological experiments, including the labeled release experiment, which was designed to detect metabolic activity. In this experiment, simple 14 C‐labeled substrates, water, and Martian soil were combined and monitored for the evolution of radioactive gases (Levin and Stratt ) as evidence that microorganisms had metabolized the substrate. Viking instruments detected 14 C labeled gas; however, it is widely accepted that those data were due to oxidizing agents in the regolith rather than microbial activity (Lasne et al.…”
Section: Objective 2: Assess and Interpret The Potential Biological Hmentioning
confidence: 99%
“…The most interesting results came from the Labelled Release Experiment (LR) which showed reactivity similar to that expected from microorganisms. 8 However, it is generally held that the reactions in the LR instrument and the other results from Viking can be explained by the chemistry of perchlorate now known to be on Mars. 9 However, the conclusion that the surface of Mars is devoid of life is tentative.…”
Section: Second Lifementioning
confidence: 99%
“…Past trial of direct detection of life on Mars by the 1970's Viking mission resulted in a negative conclusion, 1) whereas numbers of circumstances provided by recent exploration missions in the last decade indicated that there are good reasons to perform another life detection program. 2) Recent explorations have provided evidence for 1) the existence of large bodies of ancient surface water (paleo-ocean/lakes), [10][11][12] 2) a limited but certain period of wet and warm paleo-climate probably suitable for life, 13) and 3) the existence of strong magnetic field that could have protected the atmosphere from being quickly eroded away in the earliest stage of the Mars history (Noachian: 4.5 Ga to ~4.2 Ga). 14) These would lead one to argue that the surface environment (e.g., hydrologic activity) in ancient Mars was not very different from that for Earth.…”
Section: Mars As the First Target Of Search For Lifementioning
confidence: 99%
“…1) Since then, numbers of new finding provided by recent Mars exploration missions indicate that there are good reasons to perform another life detection program. 2) The sensitivity of the GC-MS (mass spectrometer) onboard the Viking lander was not high enough to detect <10 6 microbial cells in 1 gram soil. 3,4) Here we propose Life Detection Microscope (LDM) that has the potential sensitivity much higher than the instrument onboard Viking.…”
Section: Introductionmentioning
confidence: 99%